Unprecedented silicon(II)→calcium complexes with N-heterocyclic silylenes - Blom, Burgert; Klatt, Günter; Gallego, Daniel; Tan, Gengwen; Driess, Matthias (Dalton transactions, 2015)
The first N-heterocyclic silylene (NHSi) complexes of any s-block element to date are reported for calcium: [(η5-C5Me5)2Ca←:Si(O-C6H4-2-tBu){(NtBu)2CPh}] (6) and [(η5-C5Me5)2Ca←:Si(NtBuCH)2] (7). Complexes 6 and 7 are isolable in a facile way upon reaction of the corresponding free N-heterocyclic silylenes (NHSis) with [(η5-C5Me5)2Ca] (2). Complexes 6 and 7 were fully characterised by spectroscopic means and the single crystal X-ray diffraction analysis of 6 is also reported. Analysis of the bonding situation by DFT methods including a Bader Atoms in molecules (AIM) analysis is also reported. The bonding interaction between the Si and Ca centres in complexes 6 and 7 can best be viewed as σ-donor-acceptor interactions, with a considerable ionic contribution in the bond. The reactivity towards the oxygen containing substrates THF and benzophenone is also discussed.
First published 4 November 2014
Gesehen am 26.05.2020